Translesional synthesis on a DNA template containing N(2)-methyl-2′-deoxyguanosine catalyzed by the Klenow fragment of Escherichia coli DNA polymerase I - Yasui, Manabu (Oxford University Press, 2001)
Formaldehyde is produced in most living systems and is present in the environment. Evidence that formaldehyde causes cancer in experimental animals infers that it may be a carcinogenic hazard to humans. Formaldehyde reacts with the exocyclic amino group of deoxyguanosine, resulting in the formation of N(2)-methyl-2′-deoxyguanosine (N(2)-Me-dG) via reduction of the Schiff base. The same reaction is likely to occur in living cells, because cells contain endogenous reductants such as ascorbic acid and gluthathione. To explore the miscoding properties of formaldehyde-derived DNA adducts a site-specifically modified oligodeoxynucleotide containing a N(2)-Me-dG was prepared and used as the template in primer extension reactions catalyzed by the Klenow fragment of Escherichia coli DNA polymerase I. The primer extension reaction was slightly stalled one base before the N(2)-Me-dG lesion, but DNA synthesis past this lesion was readily completed. The fully extended products were analyzed to quantify the miscoding specificities of N(2)-Me-dG. Preferential incorporation of dCMP, the correct base, opposite the lesion was observed, along with small amounts of misincorporation of dTMP (9.4%). No deletions were detected. Steady-state kinetic studies indicated that the frequency of nucleotide insertion for dTMP was only 1.2 times lower than for dCMP and the frequency of chain extension from the 3′-terminus of a dT:N(2)-Me-dG pair was only 2.1 times lower than from a dC:N(2)-Me-dG pair. We conclude that N(2)-Me-dG is a miscoding lesion capable of generating G→A transition mutations.